PERAN GURU DALAM MEMBERIKAN BIMBINGAN KEPADA ANAK YANG BERPERILAKU BERMASALAH DI SD INPRES 03 LEMBUR BARAT - Asrina Takalapeta; Ribka Maukaling, Agustinus menase Meimakani, Yessy Mata, Petrus Mau Tellu Dony, Yermia S. Wabang (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to examine the role of teachers in providing guidance to children who behave problematically in elementary schools, especially at SD INPRES 03 Lembur Barat, Alor Regency. Children who show problematic behaviors, such as aggressiveness, disobedience, lack of responsibility, lack of attendance in class and disturbance to peers, are challenges to the learning process and a conducive classroom climate. The implementation of guidance at the elementary school level in general is still faced with various obstacles, such as limited teachers' understanding of behavior guidance strategies, the absence of special BK teachers, and the lack of parental involvement in the mentoring process. This study uses a qualitative approach with a case study method. The data collection technique was carried out through observation and in-depth interviews with classroom teachers to explore their role in dealing with students' problematic behaviors. Data were analyzed using qualitative descriptive techniques. The results of the study show that teachers have a central role as a behavior guide, both through individual and group approaches. Teachers not only play the role of teachers, but also as character builders who provide guidance through intracurricular activities. In intracurricular activities, teachers integrate social values, discipline, and responsibility into learning. Teachers also facilitate the formation of attitudes and emotional control of students. This research contributes to strengthening the role of teachers as facilitators of the formation of positive behavior in children from an early age, as well as as a reference for the development of behavior guidance programs in elementary schools.